Embryonic and fetal evaluation by ultrasound in crossbred dairy cows submitted to artificial insemination or artificial insemination in a fixed time - de Andrade, Rodrigo B.; da Silva, Vinícius Cunha Figueiredo; da Silva, Andressa Ferreira; Caldas, Saulo Andrade; da Costa, Orlando Marques; Abidu-Figueiredo, Marcelo; Palhano, Helcimar Barbosa (Brazilian Journal of Veterinary Medicine, 2018)
Between the years 2013 and 2016 were used 31 crossbred cows of Gir and Dutch races, at different stages of gestation, multipara aged 4 and 8 years and body condition score (BCS) average 3 on a scale that ranged from 1 to 5 (1 very lean and 5 very fat) of the Federal Rural University of milk cattle production sector of Rio de Janeiro, Seropédica, RJ, in order to evaluate the embryonic and fetal development compared between insemination conventional Artificial (IA) and Artificial Insemination Fixed Time (TAI). Development parameters were evaluated axial and appendicular skeleton, as well as the allantois, amnion, and heart rate. The data obtained over the three years of evaluation in this study showed that ultrasound B-mode via transrectal, is a safe tool for pregnancy monitoring in the first trimester of the evaluated females, and the variables analyzed high reliability for the study of embryo viability and fetal bovine in the first trimester of pregnancy. The use of hormones for synchronization of ovulation and TAI did not influence the embryonic and fetal development of crossbred dairy cows, concluding that products from conventional AI and TAI present development pattern in the first trimester of pregnancy with no significant differences.